2004
DOI: 10.1002/bdd.390
|View full text |Cite
|
Sign up to set email alerts
|

In vitro dissolution and in vivo oral absorption of methylphenidate from a bimodal release formulation in healthy volunteers

Abstract: Following a single oral drug administration, Ritalin LA demonstrated a two-peak plasma concentration-time profile, similar to that of the IR formulation given 4 h apart, but with less fluctuation in the plasma concentration-time profile. The in vivo biphasic absorption of MPH appeared to be well correlated with the bimodal dissolution characteristics of this new Ritalin LA formulation, and some changes in the dissolution profiles for the DR beads appeared not to affect the overall bioavailability of MPH in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…concluded that the three formulations were bioequivalent despite a different shape of the PK time courses. It should be noted that the criteria used by Wang et al . to assess the bioequivalence of MPH formulations (Ritalin LA) are not the same as the current recommendations of the FDA .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…concluded that the three formulations were bioequivalent despite a different shape of the PK time courses. It should be noted that the criteria used by Wang et al . to assess the bioequivalence of MPH formulations (Ritalin LA) are not the same as the current recommendations of the FDA .…”
Section: Discussionmentioning
confidence: 99%
“…The original study enrolled 17 participants in a fourtreatment, four-period, single-dose, randomized crossover design study, but only 16 subjects were retained for the final PK analysis. 11 The subjects received four treatments, after at least a 10-hour fast, 3 Ritalin LA capsule formulations (40 mg) and Ritalin IR tablets (two 20 mg given 4 hours apart) as the reference. The three Ritalin LA formulations were selected to provide slow-release, medium-release, and fast-release in vitro dissolution rates, respectively.…”
Section: Methods Datamentioning
confidence: 99%
See 1 more Smart Citation
“…12,89,90,91,92 In addition, an IVIVC should not be developed using plasma concentrations of racemate when there are stereoselective dissolution or absorption differences between the two enantiomers. 93 More importantly, the dissolution process should be the rate-limiting step in the absorption process, as discussed previously. In most cases, IVIVC models are being established using average in vivo response, thus ignoring the inter-and intra-subject variability.…”
Section: Limitations and Additional Considerationsmentioning
confidence: 97%
“…Optimal dosage included achieving a balance of maximizing effectiveness for symptom relief while minimizing negative side effects. For the first EEG acquisition, all shortacting stimulant medications were discontinued for at least 24 hours prior to the assessment, which is considered to be an adequate amount of time for the stimulant to be out of the participants' systems, and therefore not impact the EEG data (Wang et al, 2003). No participants were currently taking long-acting stimulant medications.…”
Section: Methodsmentioning
confidence: 99%